Linking Tarim Basin sea retreat (west China) and Asian aridification in the late Eocene. (5th March 2014) - Bosboom, R.; Dupont‐Nivet, G.; Grothe, A.; Brinkhuis, H.; Villa, G.; Mandic, O.; Stoica, M.; Huang, W.; Yang, W.; Guo, Z.; Krijgsman, W.
Abstract The Tarim Basin in western China formed the easternmost margin of a shallow epicontinental sea that extended across Eurasia and was well connected to the western Tethys during the Paleogene. Climate modelling studies suggest that the westward retreat of this sea from Central Asia may have been as important as the Tibetan Plateau uplift in forcing aridification and monsoon intensification in the Asian continental interior due to the redistribution of the land‐sea thermal contrast. However, testing of this hypothesis is hindered by poor constraints on the timing and precise palaeogeographic dynamics of the retreat. Here, we present an improved integrated bio‐ and magnetostratigraphic chronological framework of the previously studied marine to continental transition in the southwest Tarim Basin along the Pamir and West Kunlun Shan, allowing us to better constrain its timing, cause and palaeoenvironmental impact. The sea retreat is assigned a latest Lutetian–earliest Bartonian age (ca. 41 Ma; correlation of the last marine sediments to calcareous nannofossil Zone CP14 and correlation of the first continental red beds to the base of magnetochron C18r). Higher up in the continental deposits, a major hiatus includes the Eocene–Oligocene transition (ca. 34 Ma). This suggests the Tarim Basin was hydrologically connected to the Tethyan marine Realm until at least the earliest Oligocene and had not yet been closed by uplift of the Pamir–Kunlun orogenic system. The westward sea retreat at ca. 41 Ma and the disconformity at the Eocene–Oligocene transition are both time‐equivalent with reported Asian aridification steps, suggesting that, consistent with climate modelling results, the sea acted as an important moisture source for the Asian continental interior.